Técnicas ópticas para o controle microbiológico de sangue - Corrêa, Thaila Quatrini (2017)
Blood, considered a highly nutritive medium, can be the target of bacterial, fungal, viral and parasitic contamination. Blood bags containing erythrocytes, platelets, and plasma, used in hemotherapy for transfusion, are also targets of contamination, which can trigger serious diseases, especially blood infections. When these infections are not detected or treated rapidly, they can progress to sepsis, a leading cause of death in intensive care units. Some optical techniques may be used in the microbiological control of blood. In this study, photodynamic inactivation and ultraviolet radiation were evaluated in the in vitro decontamination of whole blood, erythrocytes, and platelet-rich plasma with Staphylococcus aureus, one of the main bacteria related to these infections. For photodynamic inactivation of S. aureus, Photogem® with 630 nm light and Photodithazine® with 660 nm light were evaluated in PBS and whole blood, with toxicity determined by hemolysis and cell viability assays. Photogem® showed a lower hemolysis rate for erythrocytes (10.7%) evaluated in whole blood, compared to Photodithazine® (55.7%), so the other tests were performed only with Photogem®. The reductions of S. aureus in PBS, whole blood, erythrocytes, and platelet-rich plasma at 15 J/cm2 and 50 μg/mL were 7.2 log10, 1.0 log10, 1.3 log10 and 0.4 log10 CFU/mL, respectively. Quantitative and qualitative analyses of whole blood were normal. However, erythrocytes hemolysis, in the absence of plasma, was 100%. The cell viability assay showed high apoptosis rates in the isolated erythrocytes, indicating the destructive action of this technique, but normal platelet viability. Photogem® analysis with whole blood showed greater interaction with plasma, however, in the absence of plasma, Photogem® accumulated on the erythrocyte membrane. For UVC radiation (254 nm), different light doses were analyzed in S. aureus in PBS and whole blood, and the cell viability assay determined the toxicity of the technique. The reductions of S. aureus in PBS, whole blood, erythrocytes and platelet-rich plasma were 6.5 log10 (0.78 J/cm2), 1.7 log10 (23 J/cm2), 1.1 log10 (21 J/cm2) and 2.5 log10 CFU/mL (23 J/cm2), respectively. The relatively small differences in plasma uptake as a function of irradiation time were observed, suggesting little degradation of plasma proteins after irradiation with the maximum light dose (23 J/cm2). The cell viability assay showed normal rates for erythrocytes at 23 J/cm2, suggesting no damage in these cells. However, in the platelets, a high apoptosis rate was observed, indicating damage to these cell fragments in the highest light dose studied. Therefore, the optical techniques showed opposite damage effects in each blood component, and according to the decontaminated target, the use of one or another technique should be evaluated together with the best microbial inactivation and blood components preservation conditions to ensure microbiological control of blood.